Metastasis of two malignant tumors of different genesis in axillary lymph node (a case report) - Rusin, A.V.; Petrosov, O.V.; Chumak, A.I.; Kushnir, V.M. (Experimental Oncology, 2016)
This case report describes a rare clinical condition: metastasis of synchronous multiple primary tumors — skin melanoma and breast cancer in one axillary lymph node, confirmed with the results of clinical, morphological and immunohistochemical study of surgical material from 40 year-old woman.